Cross-linguistic evidence for memory storage costs in filler-gap dependencies with wh-adjuncts - Stepanov, Artur; Stateva, Penka (Frontiers in Psychology, 2015)
This study investigates processing of interrogative filler-gap dependencies in which the filler integration site or gap is not directly subcategorized by the verb. This is the case when the wh-filler is a structural adjunct such as how or when rather than subject or object. Two self-paced reading experiments in English and Slovenian provide converging cross-linguistic evidence that wh-adjuncts elicit a kind of memory storage cost similar to that previously shown in the literature for wh-arguments. Experiment 1 investigates the storage costs elicited by the adjunct when in Slovenian, and Experiment 2 the storage costs elicited by how quickly and why in English. The results support the class of theories of storage costs based on the metric in terms of incomplete phrase structure rules or incomplete syntactic head predictions. We also demonstrate that the endpoint of the storage cost for a wh-adjunct filler provides valuable processing evidence for its base structural position, the identification of which remains a murky issue in current grammatical research.